INVENTARISASI JAMUR PADA BAWANG MERAH (Allium ascalonicum L.) YANG DIJUAL DIBEBERAPA PASAR DI KOTA PADAN - Wirdawati, Yenni - (Pendidikan Biologi, 2014)
Red Onion is annual crops. The plants is chacaterized with shaped clumps, fiber roots, very short trunk barely visible, and the leaves are elongated cylindrical shape. Red Onion contain vitamin C, potassium, fiber, and folic acid. Beside of that, red onion also contain calcium and iron. Red onion is very easily contaminated by fungi. Red onions damage are caused by fungi that occurs in post-harvest which is influenced by environmental and storage condition were not as good as that seen in traditional markets and dirty and also wet marketâs condition, can cause red onions are contaminated by fungi. Red onions which are contaminated by fungi causing rot of onion and no longer in demand by consumers, and can cause substantial losses to traders. This study aims to inventory the types of fungi found in red onions.This research was conducted at the Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences Andalas University Padang. The research was conducted in February and March 2014. This study used a descriptive survey method, namely by direct observation in the field using contaminated onions and mushrooms cultured in the laboratory to obtain pure cultures and identified macroscopically and microscopically. Research results indicate that the fungus is present in onion (Allium ascalonicum L.) which are sold in several markets in Padang, including Aspergillus niger, Aspergillus ochraceus, Aspergillus parasiticus, Penicillium sp and Penicillium expansum.